A small interfering RNA screen of genes involved in DNA repair identifies tumor-specific radiosensitization by POLQ knockdown - Higgins, Geoff S; Prevo, Remko; Lee, Yin-Fai; Helleday, Thomas; Muschel, Ruth J; Taylor, Steve; Yoshimura, Michio; Hickson, Ian D; Bernhard, Eric J; McKenna, W Gillies (Cancer research (Chicago, Ill.), 2010)
The effectiveness of radiotherapy treatment could be significantly improved if tumor cells could be rendered more sensitive to ionizing radiation (IR) without altering the sensitivity of normal tissues. However, many of the key therapeutically exploitable mechanisms that determine intrinsic tumor radiosensitivity are largely unknown. We have conducted a small interfering RNA (siRNA) screen of 200 genes involved in DNA damage repair aimed at identifying genes whose knockdown increased tumor radiosensitivity. Parallel siRNA screens were conducted in irradiated and unirradiated tumor cells (SQ20B) and irradiated normal tissue cells (MRC5). Using gammaH2AX foci at 24 hours after IR, we identified several genes, such as BRCA2, Lig IV, and XRCC5, whose knockdown is known to cause increased cell radiosensitivity, thereby validating the primary screening end point. In addition, we identified POLQ (DNA polymerase ) as a potential tumor-specific target. Subsequent investigations showed that POLQ knockdown resulted in radiosensitization of a panel of tumor cell lines from different primary sites while having little or no effect on normal tissue cell lines. These findings raise the possibility that POLQ inhibition might be used clinically to cause tumor-specific radiosensitization.